THE EFFECT OF OXYGEN IN THE CATALYTIC SYNTHESIS OF ENDOHEDRAL CARBYNE - Mehmonov, Kamoliddin; Ergasheva, Aziza; Yusupov, Maksudbek; Khalilov, Umedjon (MMIT Proceedings, 2023)
Carbyne, a novel carbon nanostructure, has drawn considerable attention in modern nanotechnology due to its unique physical properties. Despite the successful synthesis of carbyne through various methods, the mechanisms behind carbon monoxide-dependent catalytic synthesis of endohedral carbyne remain poorly understood. In this simulation-based study, we investigate the synthesis of endohedral carbyne dependent on C and CO radicals in the presence of a Ni5 catalyst inside double-walled carbon nanotubes of (5,5)@(10,10) structure. Our results show that the introduction of the C atom leads to the formation of a long carbon chain within the Ni5@(5,5)@(10,10) model system. In contrast, in the case of CO radicals, the carbyne chain growth is hindered due to the oxidation of nickel clusters by oxygen atoms after the initial nucleation stage. Our findings are consistent with previous theoretical, simulation, and experimental studies, and offer valuable insights into the synthesis of carbyne-based nanodevices for future nanotechnology.